Method for testing binding property of battery pole and epoxy resin adhesive

By testing the binding performance of lead-acid battery pole and epoxy resin glue, the problem of inaccurate measurement of binding performance in the prior art was solved, and the scientific selection of different types of epoxy resin glue was achieved, and the battery sealing performance was improved.

CN119510258APending Publication Date: 2025-02-25SHANDONG SACRED SUN POWER SOURCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411742581.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art is difficult to accurately test the binding performance of lead-acid battery pole and epoxy resin glue, which leads to uncertainty when selecting different types of epoxy resin glue, affecting the battery sealing performance.

Method used

By preparing the electrode column, wrapping the epoxy resin glue, exposing the side seams of the bonding surface, immersing it in the electrolyte for energization and corrosion, measuring the penetration height and calculating the penetration rate, to evaluate the binding performance of the electrode column and the epoxy resin glue.

Benefits of technology

This method can accurately reflect the binding performance of the pole column and epoxy resin glue, provide effective data support, help select high-quality epoxy resin glue, and improve battery sealing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510258A_ABST
    Figure CN119510258A_ABST
Patent Text Reader

Abstract

The invention discloses a method for testing the bonding property of a battery pole and epoxy resin glue, which is applied to the field of batteries and comprises the following steps: preparing a pole; wrapping the outer surface of the pole with epoxy resin glue to prepare a first sample piece; a bonding surface is arranged between the epoxy resin glue and the pole; processing the first sample piece, exposing a side seam formed by the joint surface, and manufacturing a second sample piece; immersing the second sample piece into the electrolyte, and electrifying the second sample piece for preset corrosion time, so that the electrolyte is immersed into the junction surface from the side seam; and measuring the permeation height of the junction surface in the second sample piece, and determining the permeation rate of the pole according to the ratio of the permeation height to the corrosion time. The side seam of the bonding surface between the pole and the epoxy resin adhesive is exposed, the electrolyte is used for corrosion along the side seam, and the bonding performance of the pole and the epoxy resin adhesive can be accurately reflected by the permeation rate determined according to the ratio of the permeation height to the corrosion time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a method for testing the bonding between a battery pole and epoxy resin glue. Background Art

[0002] During the use of lead-acid batteries, due to the insufficient sealing of the battery poles and poor sealing of the epoxy resin glue at the positive and negative poles, the internal sulfuric acid electrolyte will gradually overflow and penetrate along the surface of the battery poles as the use time increases. When it penetrates to the top of the lead-acid battery pole, it will cause corrosion of the pole, increase the connection resistance, and corrode the battery casing and the external environment, easily causing an external short circuit of the battery and even a fire.

[0003] The primary method for preventing battery terminal seal penetration is to optimize the sealing material and the use of epoxy resin adhesive. Epoxy resin adhesives must possess excellent mechanical properties, including high strength, high toughness, acid resistance, and fatigue resistance. They must also adhere well to metals and organic materials, with the bond surface meeting the same high strength, toughness, acid resistance, and fatigue resistance requirements as the adhesive itself. The varying quality of epoxy resin adhesives produced by domestic manufacturers has led to uncertainty regarding the bonding ability of different epoxy resin adhesives with lead-acid battery terminals, making accurate testing of these bonding abilities difficult.

[0004] In summary, how to improve the accuracy of the results of the bonding ability between lead-acid battery poles and epoxy resin glue, and provide effective data support for the selection of different types of epoxy resin glue for lead-acid battery development and sealing performance improvement, is an urgent problem that technicians in this field need to solve. Summary of the Invention

[0005] The purpose of the present invention is to provide a method for testing the bonding between a battery pole and epoxy resin glue, which can accurately measure the bonding performance between the pole and epoxy resin glue.

[0006] To solve the above technical problems, the present invention provides a method for testing the bonding between a battery terminal and epoxy resin adhesive, comprising:

[0007] Prepare the pole;

[0008] Wrapping the outer surface of the pole with epoxy resin glue to form a first sample; a bonding surface is formed between the epoxy resin glue and the pole;

[0009] processing the first sample to expose the side seam formed by the joint surface to produce a second sample;

[0010] Immersing the second sample in an electrolyte and applying electricity to the second sample for a preset corrosion time, so that the electrolyte penetrates into the bonding surface from the side seam;

[0011] The penetration height of the bonding surface in the second sample is measured, and the penetration rate of the pole is determined according to the ratio of the penetration height to the corrosion time.

[0012] Optionally, the preparing the pole includes:

[0013] preparing a plurality of the poles;

[0014] Immersing the second sample in an electrolyte and applying power to the second sample for a preset corrosion time comprises:

[0015] A plurality of the second samples are immersed in electrolyte in series and the second samples in series are energized for a preset corrosion time.

[0016] Optionally, wrapping the outer surface of the pole with epoxy resin glue to form the first sample includes:

[0017] Different types of epoxy resin glue are wrapped on the surfaces of different poles to produce a plurality of the first samples.

[0018] Optionally, the preparing the pole includes:

[0019] Grind the pole surface with sandpaper.

[0020] Optionally, wrapping the outer surface of the pole with epoxy resin glue to form the first sample includes:

[0021] The pole is placed in a sleeve and injected with corresponding epoxy resin glue, and then placed in an oven at a preset temperature for curing to produce the first sample.

[0022] Optionally, processing the first sample to expose the side seam formed by the joint surface to produce the second sample includes:

[0023] The end of the first sample is polished to expose the preset end face of the pole in the first sample to make a second sample; the edge of the end face forms the side seam.

[0024] Optionally, immersing the second sample in an electrolyte and applying power to the second sample for a preset corrosion time includes:

[0025] placing the second sample and the electrolyte into a container, and heating the container in a water bath;

[0026] The second sample is energized for a preset corrosion time.

[0027] Optionally, the water bath heating temperature ranges from 58°C to 62°C.

[0028] Optionally, the electrolyte is dilute sulfuric acid.

[0029] Optionally, applying power to the second sample for a preset corrosion time includes:

[0030] The second sample is energized with a constant current for a preset corrosion time, wherein the constant current has a value ranging from 1A to 3A.

[0031] The present invention provides a method for testing the bonding between a battery pole and epoxy resin glue, comprising: preparing a pole; wrapping the outer surface of the pole with epoxy resin glue to form a first sample; providing a bonding surface between the epoxy resin glue and the pole; processing the first sample to expose a side seam formed by the bonding surface to form a second sample; immersing the second sample in an electrolyte and energizing the second sample for a preset corrosion time, so that the electrolyte penetrates into the bonding surface from the side seam; measuring the penetration height of the bonding surface in the second sample, and determining the penetration rate of the pole based on the ratio of the penetration height to the corrosion time.

[0032] By exposing the side seam of the bonding surface between the pole and the epoxy resin glue, the electrolyte is used to corrode along the side seam. The penetration rate determined by the ratio of penetration height to corrosion time can accurately reflect the bonding performance between the two, thereby providing effective data support for the selection of different types of epoxy resin glue for battery development and sealing performance improvement. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the embodiments of the present invention or the technical solutions of the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0034] FIG1 is a flow chart of a method for testing the bonding between a battery terminal and epoxy resin adhesive provided by an embodiment of the present invention;

[0035] FIG2 is a flow chart of a method for testing the bonding between a battery terminal and epoxy resin adhesive provided by an embodiment of the present invention;

[0036] FIG3 is a schematic structural diagram of a first sample according to an embodiment of the present invention;

[0037] Figure 4 This is a schematic diagram of the corrosion structure of the second sample in an embodiment of the present invention;

[0038] Figure 5 This is a schematic diagram of the local structure of area A in Figure 3.

[0039] In the figure: 1. Terminal, 2. Epoxy resin glue, 3. Sleeve, 4. Second sample, 5. Beaker, 6. Electrolyte, 7. Galvanostat, 8. Corrosion pattern. DETAILED DESCRIPTION

[0040] The core of the present invention is to provide a method for testing the bonding between battery poles and epoxy resin glue. In the prior art, there is no good method for testing the bonding between battery poles and epoxy resin glue.

[0041] The present invention provides a method for testing the bonding between a battery pole and epoxy resin glue, comprising: preparing a pole; wrapping the outer surface of the pole with epoxy resin glue to form a first sample; providing a bonding surface between the epoxy resin glue and the pole; processing the first sample to expose a side seam formed by the bonding surface to form a second sample; immersing the second sample in an electrolyte and applying power to the second sample for a preset corrosion time, so that the electrolyte penetrates into the bonding surface from the side seam; measuring the penetration height of the bonding surface in the second sample, and determining the penetration rate of the pole based on the ratio of the penetration height to the corrosion time.

[0042] By exposing the side seam of the bonding surface between the pole and the epoxy resin glue, the electrolyte is used to corrode along the side seam. The penetration rate determined by the ratio of penetration height to corrosion time can accurately reflect the bonding performance between the two, thereby providing effective data support for the selection of different types of epoxy resin glue for battery development and sealing performance improvement.

[0043] In order to enable those skilled in the art to better understand the present invention, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0044] Example 1

[0045] Please refer to FIG. 1 , which is a flow chart of a method for testing the bonding between a battery pole and epoxy resin adhesive provided by an embodiment of the present invention.

[0046] Referring to FIG1 , in an embodiment of the present invention, a method for testing the bonding between a battery terminal and epoxy resin adhesive includes:

[0047] S101: Prepare the pole.

[0048] The battery measured in this embodiment is generally a lead-acid battery, and accordingly, the electrode 1 used in this embodiment is generally a lead electrode 1. Of course, depending on the type of battery, electrodes 1 made of other materials may also be used in this step, and the specific material of the electrode 1 is not specifically limited in this embodiment.

[0049] During the preparation of the pole 1 in this step, the surface of the pole 1 is typically polished to ensure a tight bond between the pole 1 and the epoxy resin adhesive 2. Specifically, this step typically involves polishing the surface of the pole 1 with sandpaper, specifically 400-grit and / or 1000-grit sandpaper, to ensure a smooth surface free of nicks, impurities, or pitting, thereby ensuring a tighter bond between the pole 1 and the epoxy resin adhesive 2.

[0050] S102: Wrap the outer surface of the pole with epoxy resin glue to form a first sample.

[0051] In this embodiment, the epoxy resin glue 2 forms a bonding surface with the pole 1. In this step, the epoxy resin glue 2 is coated on the outer surface of the pole 1, and the epoxy resin glue 2 and the pole 1 are well bonded at the bonding surface. Accordingly, the first sample produced in this step is the pole 1 with the epoxy resin glue 2 coated on the surface and the epoxy resin glue 2 having been cured.

[0052] S103: Processing the first sample to expose the side seam formed by the joint surface to produce a second sample.

[0053] In this step, the first sample needs to be processed, which is usually done by polishing. During the polishing process, the pole 1 is usually exposed. This process is equivalent to opening a window in a specific area of ​​the epoxy resin glue 2. When the pole 1 is exposed, the side seam formed by the above-mentioned bonding surface is also exposed. The inward extension surface of the gap is the bonding surface between the pole 1 and the epoxy resin glue 2.

[0054] S104: Immerse the second sample in the electrolyte and energize the second sample for a preset corrosion time, so that the electrolyte penetrates into the joint surface from the side seam.

[0055] In this step, the second sample 4 is immersed in electrolyte 6 and energized to simulate the battery charging process. During this process, the electrolyte 6 contacts the side seams and corrodes the terminal 1 along the seams at the joint surface. In other words, the electrolyte 6 penetrates the joint surface through the side seams, corroding the terminal 1. The current used to charge the second sample 4 in this step is typically in the range of 1A to 3A, and the continuous charging time for the entire charging process is typically no less than 360 hours.

[0056] S105: Measuring the penetration height of the bonding surface in the second sample, and determining the penetration rate of the pole according to the ratio of the penetration height to the corrosion time.

[0057] In this step, the height of the bonding surface of the second sample 4 penetrated by the electrolyte 6 after the processing of S104, that is, the penetration height, will be measured. When the pole 1 is penetrated by the electrolyte 6, it can be directly reflected from the appearance. The above-mentioned penetration height is usually also the length of the bonding surface penetrated in the direction perpendicular to the above-mentioned side seam, that is, based on the corrosion pattern 8 formed by the penetration of the electrolyte 6 into the bonding surface, the distance from the farthest point of the exposed side seam to the above-mentioned side seam. In this embodiment, the above-mentioned distance will be recorded as the penetration height. In this step, the ratio between the above-mentioned penetration height and the corrosion time recorded in S104 will be specifically used as the penetration rate of the pole 1. The penetration rate can directly reflect the bonding between the pole 1 and the epoxy resin glue 2. Obviously, the greater the penetration rate, the weaker the bonding between the pole 1 and the epoxy resin glue 2.

[0058] Specifically, the calculation formula for the penetration rate of pole 1 in this embodiment is:

[0059] V ~ =H / t;

[0060] In the above formula, V ~ represents the penetration rate of pole 1; H represents the penetration height of the joint surface; t represents the corrosion time.

[0061] Based on the lead-acid battery, the electrolyte 6 used in this embodiment can be dilute sulfuric acid, which has a density of 1.28 g / cm 3 (25°C). Of course, depending on the type of battery to be tested, other types of electrolyte 6 may also be used to corrode the electrode 1 in this embodiment, and this is not specifically limited here. The above-mentioned penetration height can be measured manually using a digital vernier caliper or a vernier caliper such as an arc vernier caliper.

[0062] The above process can measure the bonding strength of a specific epoxy resin adhesive 2 with the pole 1, and the above penetration rate can reflect the bonding strength of the epoxy resin adhesive 2 with the pole 1. For different types of epoxy resin adhesives 2, their penetration rates can be measured based on the above process to determine the bonding strength of each epoxy resin adhesive 2 with the technology.

[0063] This embodiment provides a method for testing the bonding performance between a battery pole 1 and epoxy resin glue 2. By exposing the side seam of the bonding surface between the pole 1 and the epoxy resin glue 2, an electrolyte 6 is used to corrode along the side seam. The penetration rate determined by the ratio of the penetration height to the corrosion time can accurately reflect the bonding performance between the two, thereby providing effective data support for the selection of different types of epoxy resin glue 2 for battery development and sealing performance improvement.

[0064] The specific content of the testing method for the bonding between the battery pole 1 and the epoxy resin glue 2 provided by the present invention will be described in detail in the following invention embodiments.

[0065] Example 2

[0066] Please refer to Figures 2 to Figure 5 , FIG2 is a flow chart of a method for testing the bonding between a battery terminal and epoxy resin adhesive provided by an embodiment of the present invention; FIG3 is a schematic structural diagram of a first sample in an embodiment of the present invention; Figure 4 This is a schematic diagram of the corrosion structure of the second sample in an embodiment of the present invention; Figure 5 This is a schematic diagram of the local structure of area A in Figure 3.

[0067] 2 , in an embodiment of the present invention, a method for testing the bonding between a battery terminal and epoxy resin adhesive includes:

[0068] S201: Prepare multiple poles.

[0069] This step can specifically prepare multiple poles 1 so that the bonding properties of multiple epoxy resin adhesives 2 to the poles 1 can be tested simultaneously. In this embodiment, the poles 1 are typically cylindrical poles 1, typically having a height of approximately 60 mm and a diameter of approximately 10 mm. Of course, the shape and size of the poles 1 are not specifically limited in this embodiment and will vary depending on the specific circumstances. The specific details of polishing the poles 1 have been detailed in the above embodiments and will not be repeated here.

[0070] S202: Different types of epoxy resin adhesives are coated on the surfaces of different poles to produce a plurality of first samples.

[0071] For multiple poles 1, this step will wrap different types of epoxy resin glue 2 on the surfaces of different poles 1, that is, one type of epoxy resin glue 2 is wrapped on the surface of one pole 1, and multiple types of epoxy resin glue 2 are wrapped on the surfaces of multiple poles 1. In this embodiment, the bonding between multiple types of epoxy resin glue 2 and the poles 1 can be tested simultaneously.

[0072] Referring to Figure 3 , the process of wrapping the surface of any pole 1 with epoxy resin glue 2 may specifically include: placing the pole 1 into a sleeve 3 and injecting the corresponding epoxy resin glue 2, followed by curing in an oven at a preset temperature to produce the first sample. Specifically, a sleeve 3 may be prepared in advance, followed by placing the pole 1 into the sleeve 3 and injecting the epoxy resin glue 2 into the sleeve 3, followed by high-temperature curing to ensure a tight bond between the pole 1 and the epoxy resin glue 2. When epoxy resin glue 2 is required on multiple poles 1, the poles 1 must first be numbered. The reason for using an oven for heating in this step is that a sufficiently high temperature is required for the complete bonding chemical reaction between the epoxy resin glue 2 and the surface of the pole 1, such as the lead pole 1. A suitably high temperature also softens the glue layer, increasing wetting of the lead pole 1 surface, facilitating molecular movement, and improving adhesion to the lead pole 1. After the epoxy resin glue 2 solidifies, the first sample can be removed from the sleeve 3. In this step, the epoxy resin adhesive 2 coated on the surface of the terminal 1 is generally about 5 mm thick. When multiple first samples are produced, it is generally necessary to ensure that the thickness of the epoxy resin adhesive 2 in different first samples is roughly the same. The morphology of the first sample is similar to that of the terminal 1. For example, if the terminal 1 is cylindrical, the corresponding first sample will also be cylindrical.

[0073] S203: Grinding the end of the first sample to expose the preset end face of the pole in the first sample to produce a second sample.

[0074] In this embodiment, the edge of the end face forms the side seam. For the first cylindrical sample, in this step, the end of the first sample is polished, specifically the end face of the first sample, thereby exposing the end face of the pole 1 in the first sample. During the polishing process, the epoxy resin glue 2 on the end face of one side of the pole 1 is removed. At this time, the side seam is formed at the edge of the exposed end face of the pole 1, forming the second sample 4. Except for the exposed end face of the pole 1, the remaining surface of the pole 1 is generally covered with the epoxy resin glue 2.

[0075] Specifically, in this step, the epoxy resin glue 2 on the bottom of the first sample is usually cleaned to expose the terminal 1. The exposed end surface of the terminal 1 is then polished with 400-grit and / or 1000-grit sandpaper until the bottom surface of the terminal 1 is free of nicks and pitting. Afterwards, the surface of the sample is cleaned of debris and wiped with a cotton ball soaked in ethanol to remove surface oil. The sample is then rinsed with distilled water and dried with filter paper to produce the second sample 4.

[0076] S204: immersing a plurality of second samples in series into the electrolyte and applying power to the second samples in series for a preset corrosion time.

[0077] See also Figure 4In this step, multiple second samples 4 will be connected in series, and then each second sample 4 will be placed in a separate container and immersed in the electrolyte 6. In this step, the second samples 4 connected in series can be energized to ensure that the current flowing through each second sample 4 is equal. Generally, in this embodiment, the first second sample 4 and the last second sample 4 in series can be connected to the positive and negative poles of the constant current meter 7 respectively, and the multiple second samples 4 in series are powered by the constant current meter 7. This structure can ensure that the current flowing through each second sample 4 is the same. The connector between the second sample 4 and the constant current meter 7 usually needs to be covered with insulating tape to avoid leakage.

[0078] Specifically, in this embodiment, to accelerate the corrosion rate of the electrolyte 6, the second sample 4 and the electrolyte 6 can be heated in a water bath while the second sample 4 is powered. Specifically, this step may include: placing the second sample 4 and the electrolyte 6 in a container, heating the container in a water bath; and powering the second sample 4 for a predetermined corrosion time. Heating in a water bath can accelerate the corrosion rate and reduce the required corrosion time.

[0079] Specifically, in this step, each of the four second samples 4 can be placed in a corresponding 500ml beaker 5. 200ml of dilute sulfuric acid is added to each beaker 5 as the electrolyte 6. Each beaker 5 containing the second sample 4 is then placed in a constant-temperature water bath for heating. The increased temperature increases the electrochemical reaction rate, accelerating the erosion rate and the convection and diffusion capacity of the solution, thereby accelerating the verification of the bonding ability of the epoxy resin glue 2 to the lead terminal 1. Due to factors such as ambient temperature, dilute sulfuric acid, and beaker 5 (which affect thermal conductivity), the temperature of the dilute sulfuric acid in the water bath and inside the beaker 5 can differ significantly. Therefore, a temperature difference test is typically performed before the experiment to ensure that the water bath temperature is equal to the temperature of the electrolyte 6 in the beaker 5. In this embodiment, the water bath heating temperature typically ranges from 58°C to 62°C.

[0080] In this embodiment, a constant current can be used to energize the second sample 4 to achieve a preset corrosion time. The value range of the constant current is 1A to 3A. In this embodiment, a constant current meter 7 can be used to provide the above-mentioned constant current to the second sample 4 connected in series. In this step, it is necessary to turn on the constant current meter 7, use a thermometer to measure the temperature of the dilute sulfuric acid inside the beaker 5 within the range of 60±2°C, set the current size and continuous charging time of the constant current meter 7, record the start time of the experiment, observe and record the phenomenon that occurs after the second sample 4 invades the dilute sulfuric acid and is powered on, measure the temperature of the dilute sulfuric acid in the beaker 5 at regular intervals, track the changes in the water level of the water bath and the amount of dilute sulfuric acid in the beaker 5 during the test, maintain the water level of the water bath, and add dilute sulfuric acid to the beaker 5 when necessary to ensure the normal progress of the experiment.

[0081] S205: Measuring the penetration height of the bonding surface in the second sample, and determining the penetration rate of the pole according to the ratio of the penetration height to the corrosion time.

[0082] In this step, it is first necessary to turn off the constant current meter 7, take out the second sample 4, clean its surface with acid, and remove the epoxy resin glue 2 on the surface of the second sample 4 to expose its bonding surface, which has a pattern of the pole 1 corroded by the electrolyte 6.

[0083] See also Figure 5 In this step, a vernier caliper is used to measure the penetration height of the bonding surface in the second sample 4, recorded as H. The penetration rate of the electrode 1 is then determined based on the ratio of the penetration height to the corrosion time. The specific details of the penetration height, corrosion time, and penetration rate have been detailed in the above embodiment and will not be repeated here.

[0084] Through the above process, this embodiment can simultaneously conduct multiple experiments on the bonding ability of epoxy resin glue 2 from different manufacturers with the pole 1, and then select the optimal epoxy resin glue 2, further improve the sealing performance of the lead-acid battery pole 1, reduce the risk of lead-acid battery electrolyte 6 overflowing and penetrating through the pole 1, and improve the quality and performance of the battery.

[0085] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0086] Finally, it should be noted that, in this document, relational terms such as first and second, etc., are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any actual relationship or order between these entities or operations. Moreover, the terms "comprises," "comprising," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or device comprising a series of elements includes not only those elements, but also other elements not explicitly listed, or elements inherent to such process, method, article, or device. In the absence of further limitations, an element defined by the phrase "comprising a ..." does not exclude the presence of additional identical elements in the process, method, article, or device comprising the element.

[0087] The above is a detailed introduction to the method for testing the bonding between a battery terminal and epoxy resin glue provided by the present invention. This article uses specific examples to illustrate the principles and implementation methods of the present invention. The description of the above examples is only used to help understand the method of the present invention and its core concept. It should be pointed out that for ordinary technicians in this technical field, without departing from the principles of the present invention, several improvements and modifications can be made to the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.

Claims

1. A method for testing the bonding between a battery pole and epoxy resin adhesive, characterized in that: include: Prepare poles; Wrapping the outer surface of the pole with epoxy resin glue to form a first sample; There is a bonding surface between the epoxy resin glue and the pole; Processing the first sample to expose the side seam formed by the joint surface to produce a second sample; Immersing the second sample in an electrolyte and applying electricity to the second sample for a preset corrosion time, so that the electrolyte penetrates into the bonding surface from the side seam; The penetration height of the bonding surface in the second sample is measured, and the penetration rate of the pole is determined according to the ratio of the penetration height to the corrosion time.

2. The method according to claim 1, characterized in that The preparation of the pole comprises: preparing a plurality of the poles; Immersing the second sample in an electrolyte and applying power to the second sample for a preset corrosion time comprises: A plurality of the second samples are connected in series and immersed in an electrolyte, and the second samples connected in series are energized for a preset corrosion time.

3. The method according to claim 2, characterized in that The outer surface of the pole is coated with epoxy resin glue to make a first sample comprising: Different types of epoxy resin adhesives are coated on the surfaces of different poles to manufacture a plurality of the first samples.

4. The method according to claim 1, characterized in that The preparation of the pole comprises: Grind the pole surface with sandpaper.

5. The method according to claim 1, characterized in that The outer surface of the pole is coated with epoxy resin glue to make a first sample comprising: The pole is placed in a sleeve and injected with corresponding epoxy resin glue, and then placed in an oven at a preset temperature for curing to produce the first sample.

6. The method according to claim 1, characterized in that Processing the first sample to expose the side seam formed by the joint surface, and manufacturing the second sample comprises: The end of the first sample is polished to expose the preset end face of the pole in the first sample, so as to manufacture the second sample; the edge of the end face forms the side seam.

7. The method according to claim 1, characterized in that Immersing the second sample in an electrolyte and applying power to the second sample for a preset corrosion time comprises: Putting the second sample and the electrolyte into a container, and heating the container in a water bath; The second sample is energized for a preset corrosion time.

8. The method according to claim 7, characterized in that The temperature range of the water bath heating is 58°C to 62°C.

9. The method according to claim 1, characterized in that: The electrolyte is dilute sulfuric acid.

10. The method according to claim 1, characterized in that The step of electrifying the second sample to achieve a preset corrosion time comprises: The second sample is energized with a constant current for a preset corrosion time, wherein the constant current has a value ranging from 1A to 3A.